Nontuberculous Mycobacteria Infections at a Provincial Reference Hospital, Cambodia - Bonnet, Maryline; San, Kim Chamroeun; Pho, Yati; Sok, Chandara; Dousset, Jean-Philippe; Brant, William; Hurtado, Northan; Eam, Khun Kim; Ardizzoni, Elisa; Heng, Seiha; Godreuil, Sylvain; Yew, Wing-Wai; et al. (Emerging infectious diseases, 2017)
Prevalence of nontuberculous mycobacteria (NTM) disease is poorly documented in countries with high prevalence of tuberculosis (TB). We describe prevalence, risk factors, and TB program implications for NTM isolates and disease in Cambodia. A prospective cohort of 1,183 patients with presumptive TB underwent epidemiologic, clinical, radiologic, and microbiologic evaluation, including >12-months of follow-up for patients with NTM isolates. Prevalence of NTM isolates was 10.8% and of disease was 0.9%; 217 (18.3%) patients had TB. Of 197 smear-positive patients, 171 (86.8%) had TB confirmed (167 by culture and 4 by Xpert MTB/RIF assay only) and 11 (5.6%) had NTM isolates. HIV infection and past TB were independently associated with having NTM isolates. Improved detection of NTM isolates in Cambodia might require more systematic use of mycobacterial culture and the use of Xpert MTB/RIF to confirm smear-positive TB cases, especially in patients with HIV infection or a history of TB.